The effect of rapid strength training in a water environment according to the Obstructive force index on some kinematic variables for the start phase and achievement of the 100-meter Sprint - Mahmoud, Abu Al-Hassan; Yasir, Alaa (Journal of Physical Education, 2024)
The study aimed to prepare rapid strength training in a water environment according to the obstructive force index for 100-meter Sprint. To identify the values of some kinematic variables for the start and achievement stage for the research sample. To identify the effect of rapid strength training in a water environment in developing some kinematic variables for the start and completion stage of running ( 100 m Sprint between the test (pre-post) for the research sample. The researchers used the experimental method by designing two equal groups with a pre- and post-test to suit the nature of the research problem. The research sample was identified with track and field runners for the 100-meter event in Maysan Governorate over the age of 20 years . The number of athletes 2023-2024 is (8). They will be taken completely by the comprehensive inventory method. They constituted 100% of the research community. The researchers concluded that performing rapid strength training exercises according to the aquatic medium whose intensity is regulated according to the law of obstructive force had a positive impact on Kinematic variables for the start and completion stage. The most important recommendations which the researchers recommended are : the necessity of using rapid strength training in the aquatic medium because of this medium’s effective impact on developing muscular strength and then achievement. The of adopting the law of obstructive force to codify the training intensities for fluids (the aqueous medium) in training. Fast running and all games necessity.